THE U-SHAPED EFFECT OF CSR ON FINANCIAL PERFORMANCE OF COMPANIES IN INDONESIA DURING FINANCIAL CRISIS COVID-19 - Kasiha, Nathalia Wanda Nova; Kim, Sung Suk (Universitas Multimedia Nusantara, 2024)
Abstract - This research studies the nonlinear relationship between Corporate Social Responsibility (CSR) and the financial success of companies listed on Indonesia Stock Exchange. By analyzing 2808 observations from quarterly panel data of 145 companies over the period of 2019 to 2023, the study uses fixed effect regression model with Driscoll-Kraay method to assess how CSR impacts in nonlinearity way on Return on Asset (ROA). The result shows there’s a U-shaped relationship between CSR and ROA. At first when CSR goes up, ROA goes down. But after reaching an optimal level, CSR begins to have positive impact on ROA. Factors like company size, age, growth, leverage and liquidity have consistently shown effects on financial performance indicator in this study. When the research then specifically studies on the relationship during financial crisis era (COVID-19), it shows that the nonlinear relationship between CSR and financial performance is not significant. The results provide information for managers and policymakers to take into consideration both short term and long-term impacts on financial performance when creating CSR strategies. Keywords : CSR; Nonlinear; U-shaped; COVID-19; Financial Performance; Return on Asset, ROA